The influence of Store Atmosphere on Customers Buying Decisions at Cassava Cafe Canggu - Saraswati, Stefanie Rut; Sulistyawati, Agung Sri; Jamin Ariana, I Nyoman (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2023)
Store atmosphere is related to how managers can manipulate building design, interior space, store layout, carpet and wall textures, smells, colors, and sounds that influencer consumers that exibit certain influences. The shop atmosphere is also an important factor for prospective visitors to make purchasing decisions. The purpose of this research is to see how the shop atmosphere affects consumer purchasing decisions at Cassava Cafe Canggu. This research requires qualitative data and quantitative data where the data comes from primary data and secondary data. Primary data were extracted from questionnaires to 100 respondents who were determined by accidental sampling technicque. Quantitative data comes from Likert scale analysis and multiple linear regression analyst which tested significantly, t test, f test, and coeficient of determination. Data processing was assisted by the Statistical Package for Social Science (SPSS) version 25. Meanwhile, for testing instruments using validity, reliability and hypothesis testing. Based on the results of the analysis in study, the value of the coefficient of determination (Adj. R Square) was 0,369 which means that 36,9% of purchasing decisions were made by the shop atmosphere, while the remaining 63,1% was another variable not examined in the stud. And based on tests carried out stimultaneously between store atmosphere and purchasing decisions, it is found that the dimensions of service quality have a positive influence of 0,000 and a significant of 0,000 < 0,05.